1998
DOI: 10.1046/j.1537-2995.1998.38298193098.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of single‐donor platelets with a reduced dimethyl sulfoxide concentration by the addition of second‐messenger effectors: enhanced retention of in vitro functional activity

Abstract: The use of this platelet storage solution in the cryopreservation of platelets yields a significant improvement in their postthaw in vitro recovery and allows for a reduction of the DMSO concentration from 6 to 2 percent, with superior maintenance of in vitro viability and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 36 publications
2
43
2
Order By: Relevance
“…ThromboSol TM is a platelet‐stabilizing solution consisting of selected second‐messenger effectors that inhibit specific activation pathways endogenous to platelets, resulting in platelets that are biochemically stabilized against the detrimental effects of cold storage (Connor et al , 1996; Currie et al , 1998). Recent studies have demonstrated that the use of ThromboSol in the cryopreservation of platelets allowed simple processing, a reduction of the DMSO to 2% and excellent post‐thaw retention of cell number and in vitro functional activity (Currie et al , 1998). Specifically, when compared to platelets cryopreserved using 6% DMSO, single donor unit platelets cryopreserved with ThromboSol yielded statistically significant higher retention of cell number, percentage of cells displaying a discoid morphology, ESC and HSR (Currie et al , 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ThromboSol TM is a platelet‐stabilizing solution consisting of selected second‐messenger effectors that inhibit specific activation pathways endogenous to platelets, resulting in platelets that are biochemically stabilized against the detrimental effects of cold storage (Connor et al , 1996; Currie et al , 1998). Recent studies have demonstrated that the use of ThromboSol in the cryopreservation of platelets allowed simple processing, a reduction of the DMSO to 2% and excellent post‐thaw retention of cell number and in vitro functional activity (Currie et al , 1998). Specifically, when compared to platelets cryopreserved using 6% DMSO, single donor unit platelets cryopreserved with ThromboSol yielded statistically significant higher retention of cell number, percentage of cells displaying a discoid morphology, ESC and HSR (Currie et al , 1998).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that the use of ThromboSol in the cryopreservation of platelets allowed simple processing, a reduction of the DMSO to 2% and excellent post‐thaw retention of cell number and in vitro functional activity (Currie et al , 1998). Specifically, when compared to platelets cryopreserved using 6% DMSO, single donor unit platelets cryopreserved with ThromboSol yielded statistically significant higher retention of cell number, percentage of cells displaying a discoid morphology, ESC and HSR (Currie et al , 1998). In addition, the ThromboSol‐treated platelets displayed a statistically relevant reduction in the expression of the activation marker P‐selectin.…”
mentioning
confidence: 99%
“…Human blood banks typically rely on fresh platelet transfusions prepared from collection of whole blood or apheresis due to the technical challenges of platelet cryopreservation, as well as the considerable loss of platelets and impaired function associated with the freeze/thaw process. 7 As apheresis is not commonly available in veterinary medicine, fresh canine platelets are predominantly collected in whole blood on an as-needed basis. In this study, PC collected via apheresis provided a high-quality product, as evaluated through in vitro functional studies and assessment of in vivo lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 Expression of P-selectin, a platelet a granule GP exteriorized to the platelet surface following granule release, is considered a marker of platelet activation. 7,20,21 In studies of cryopreserved human platelets, baseline (or unstimulated) P-selectin expression was increased (35%) compared with fresh platelets (9%), suggesting premature platelet activation during the freezethaw-wash process. 17 Cryopreserved human platelets showed reduced P-selectin expression after ADP stimulation, reflecting their decreased ability for normal activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation